Effect of Trigger Configuration on Crash Box Energy Absorption in Vehicle Collisions using MSC Dytran - Satria, Eka; Saputra, Dendi Adi; Dahlan, Hendery; Son, Lovely; Saputra, M. Fazri Irwan; Afrinaldi, Feri; Susanti, Lusi; HG, Sabri Haris (Department of Mechanical Engineering, Universitas Andalas, 2025)
Vehicle crashworthiness is a critical aspect of automotive safety engineering designed to minimize injury to occupants during collisions. This paper investigates the role of trigger mechanisms in enhancing crashworthiness by managing energy absorption and deformation during impact. Trigger mechanisms, including structural features like grooves, holes, or geometric discontinuities, initiate controlled deformation, optimizing energy dissipation. This study evaluates the effectiveness of crash boxes with various cross sections and six trigger designs: bead initiator, diamond notch, smaller thickness, circular notch, circular holes, and oval holes, to absorb energy of collision using computational software, MSC Dytran. The results show that a crash box with an octagonal section absorbs more energy than those with square, rectangular, or hexagonal sections. Among the introduced trigger designs, the models of bead initiator, circular notches, and circular holes were considerably the most effective in energy absorption.